重访“游”的主题——二十世纪四十年代中国文学的文化转型 = The theme of "travel" revisited : cultural transformation of chinese literature in the 1940s - Kong, Xinren (2010)
This dissertation begins with an examination in retrospect on studies on travel literature worldwide in the 20th century. A review of the studies on the development of Chinese travel literature during the past two decades is provided. The contributions and achievements of these studies are delineated under the following five aspects: the role of the wanderer, the impact on studies in sociology, the literary origin of the theme of vagrancy, adolescent narrative in contemporary writing, and the influence on Chinese history. The assumption is that the 1940s is a noteworthy transition period in the research of Chinese Travel literature. The intention of this dissertation is to review the diversion of 1940s novels from traditional travel themes, and investigate their eclectic adoption of western literary influence. With a rereading and reinterpreting of the themes of travel in Chinese literature, and analyzing the logic of modernity in Chinese modern novels, my research will provide a scheme for the understanding of Chinese travel literature.